Students' Attitude Toward the Use of Google Classroom in Writing Activity - Tuzsaliha, Rafiah; Talib, Ahmad; Sakkir, Geminastiti (Teacher Training and Education Faculty of Syekh-Yusuf Islamic University Tangerang, 2022)
The purpose of this research was to know the students' attitudes toward the use of google classroom in a writing activity. This research used mixed-method research. The researcher chose class XI MIPA 4 of senior high school 1 Samaturu, Kolaka. The instruments of this research were questionnaires and interviews. The result of this research revealed that the students' attitudes were generally positive toward the use of google classroom in a writing activity. It is supported by the data obtained based on the three aspects of attitude. Cognitive (60%), affective (77,3%), and behavioral (77,3%) aspects of attitude were positive. The researcher also found there are two factors that hinder the students in writing descriptive texts assigned through google classroom, they are: poor internet connection and being lazy. While the supporting factors are four, they are: the display and the feature of google classroom, good internet connection, google classroom is flexible, and a study partner. In addition, there are three strategies used by the students in writing descriptive text, they are planning, drafting, and editing. Further, in writing descriptive text assignments, there are two challenges founded by the students assigned through google classroom, they are deadline and vocabulary.